Provision of Services to The Rights of Prisoners While in Class II B Tanjung Pura Detention Centre - Redi Lukisno; H. Abdul Razak Nasution (International Journal of Sociology and Law, 2024)
The Correctional System has been able to change the prison system for the better by treating prisoners as subjects. This is where the human factor is more emphasised and prisoners are also increasingly valued. The Correctional System has been able to change the prison system for the better by treating prisoners as subjects. This is where the human factor is highlighted and prisoners are also increasingly valued. The hope is that after the prisoner leaves the correctional institution, the prisoner will not repeat the criminal act again or the prisoner has had a deterrent effect on the prisoner. The research used in this journal is normative legal research. Normative legal research is research that examines the laws and regulations that apply to a legal problem. Normative research with the object of study of legislative documents by studying and by examining library legal materials or can be called a study of legal science. Prisoners are people who are undergoing a period of punishment or punishment in the penitentiary, but however the prisoner is also a human being, so the human rights of prisoners must also be protected. Related to the provision of the rights of prisoners in the Provision of services to the rights of prisoners that have been in the Class II B Tanjung Pura Detention Centre including the revocation of conditional release, granting permission to leave the city, requests for medical recommendations given to prisoners, transfer at the request of their own legal counsel in the region or between regions, delegation of correctional client guidance, social rehabilitation for drug users, referral for further treatment outside the prison, legal consultation in the field of correctional services, legal aid facilities, conditional leave for general crimes and the assimilation of general crimes.